8(4n + 13) = 6n
Use distributive property so :8 (4n) = 32n and 8(13) = 104
32n + 104 = 6n
Subtract 32n from each side and you will get:
104 = 26n
then you divide each side by 26 and your answer will be:
n = 4
X-5+5x-12=25
x+5x=25+5+12
6x=42
x=42/6
x=7
X * x
or
x times x
or
x times itself
or
x squared
all means the same thing
Option D
Using the distributive property, -7(8x – 3) + x = -55x + 21
<em><u>Solution:</u></em>
Given that we have to use distributive property to simplify the given expression
Given expression is:
-7(8x – 3) + x
Let us first understand about distributive property
The distributive property lets you multiply a sum by multiplying each addend separately and then add the products.
<em><u>The distributive property is represented as:</u></em>
a(b + c) = ab + ac
Apply this property in given expression for -7(8x - 3)
Apply the above result in given expression
Combine the like terms. Add -56x and x
Thus the given expression is simplified. Option D is correct